Original Research: Understanding Nursing Home Staff Attitudes Toward Death and Dying. Issue 8 (August 2020) - Bui, Nhat; Halifax, Elizabeth; David, Daniel; Hunt, Lauren; Uy, Edyssa; Ritchie, Christine; Stephens, Caroline
ABSTRACT: Background: Nearly 70% of nursing home residents are eligible for palliative care, yet few receive formal palliative care outside of hospice. Little is known about nursing home staff attitudes, knowledge, skills, and behaviors related to palliative care. Methods: We administered a modified survey measuring attitudes toward death to 146 nursing home staff members, including both clinical and nonclinical staff, from 14 nursing homes. Results: Nursing home staff generally reported feeling comfortable caring for the dying, but half believed the end of life is a time of great suffering. Pain control (63%), loneliness (52%), and depression (48%) were the most important issues identified with regard to these patients, and there was ambivalence about the use of strong pain medications and the utility of feeding tubes at the end of life. Top priorities identified for improving palliative care included greater family involvement (43%), education and training in pain control (50%) and in management of other symptoms (37%), and use of a palliative care team (35%) at their facility. Conclusions: Findings show there is a need for more palliative care training and education, which should be built on current staff knowledge, skills, and attitudes toward palliative care. Abstract : In this multisite study, the authors surveyed nursing home staff to gain insight into their perspectives on end-of-life care and to identify their needs regarding palliative care education and training.